The Role of an Auditor's Expertise, Experience, and Professional Certification in Auditing Financial StatementsIn light of Information Technology and Artificial Intelligence Approaches, (A study of the perspectives of a sample of auditors in Iraq) - Mahdi Abbas Ibadi; Muhannad Abbas Ayyash (International Journal on Economics, Finance and Sustainable Development, 2026)
The purpose of this study is to to highlight the importance of expertise, experience, and professional and scientific qualifications play in the auditor's ability to employ techniques including artificial intelligence, information technology, and electronic accounting systems in the field of accounting and auditing. With the purpose of demonstrating knowledge, experience, and professional qualifications' effects and roles in the use of the previously described methods in the accounting and auditing fields, the study was initiated in light of the hypotheses that were defined for it. The theoretical aspect was utilized by the researcher in order to provide an explanation of the theoretical features that are associated with the ideas of experience and professional certification of the auditor as well as procedures involving artificial intelligence. In order to support the research hypotheses, the researcher also employed statistical techniques using the generated questionnaire form. A collection of academic specialists, auditing offices, and auditing firms made up the research sample. The study came to a number of conclusions, chief among them that the auditor's educational background and professional experience increase the accuracy of the audit process's findings and that the auditor's scientific background in artificial intelligence methods and accounting information technology, provides ample opportunity for the auditor to apply this knowledge in creating reports that enhance the audit process's quality. Among the recommendations made by the study, the most significant one was that the accounting and auditing professions must keep up with the quick changes in artificial intelligence methods and the accounting information technology environment. they also needed professional organizations that specialize keeping an eye on the previously mentioned advances in accounting and auditing regulations, and establishing standards and a framework that work with the ways these technologies are being used.